Lipid and Bile Acid Dysmetabolism in Crohn’s Disease - Koji Uchiyama; Hisashi Kishi; Wataru Komatsu; Masanori Nagao; Shuji Ohhira; Gen Kobashi (Journal of Immunology Research)
Crohn’s disease is one of the systemic autoimmune diseases. It commonly affects the small intestine and colon but may involve any portion of the gastrointestinal tract from the mouth to the anus. The most affected area by Crohn’s disease is the distal part of the small intestine, in which the bile acid molecules are most efficiently reabsorbed. Bile acids form mixed micelles together with fatty acids, which function as a transport vehicle to deliver fatty acids to the apical membrane of enterocytes for absorption. Therefore, if the terminal ileum is impaired, bile acid malabsorption may occur, which may cause congenital diarrhoea in Crohn’s disease. Similarly, the impairment of the terminal ileum also induces fatty acid malabsorption, which may influence the role of fatty acids in Crohn’s disease. In contrast, a recent study reported that multidrug resistance protein 1 (MDR1) regulated effector T-cell function in the ileum from bile acid-driven oxidative stress and MDR1 loss of function in a subset of patients with Crohn’s disease. However, the role of consumption of fatty acids in Crohn’s disease remains to be fully elucidated. This review is aimed at providing an overview of some recent developments in research of Crohn’s disease from comprehensive perspective with a focus on the connection between disease location and behaviour, lipid diets, and bile acid malabsorption.